Synthesis, characterization and antifungal activity of quaternary derivatives of chitosan on Aspergillus flavus - de Oliveira Pedro, Rafael [UNESP]; Takaki, Mirelle [UNESP]; Gorayeb, Teresa Cristina Castilho [UNESP]; Bianchi, Vanildo Luiz Del [UNESP]; Thomeo, João Cláudio [UNESP]; Tiera, Marcio José [UNESP]; de Oliveira Tiera, Vera Aparecida [UNESP] (Elsevier, 2013)
Two series of new chitosan derivatives were synthesized by reaction of deacetylated chitosan (CH) with propyl (CH-Propyl) and pentyl (CH-Pentyl) trimethylammonium bromides to obtain derivatives with increasing degrees of substitution (DS). The derivatives were characterized by 1H NMR and potentiometric titration techniques and their antifungal activities on the mycelial growth of Aspergillus flavus were investigated in vitro. The antifungal activities increase with DS and the more substituted derivatives of both series, CH-Propyl and CH-Pentyl, exhibited antifungal activities respectively three and six times higher than those obtained with commercial and deacetylated chitosan. The minimum inhibitory concentrations (MIC) were evaluated at 24, 48 and 72h by varying the polymer concentration from 0.5 to 16g/L and the results showed that the quaternary derivatives inhibited the fungus growth at polymer concentrations four times lower than that obtained with deacetylated chitosan (CH). The chitosans modified with pentyltrimethylammonium bromide exhibited higher activity and results are discussed taking into account the degree of substitution (DS). © 2012 Elsevier GmbH.
Keywords: Antifungal activity; Aspergillus flavus; Chitosan; Derivatives; Mycotoxins; Anti-fungal activity; Chitosan derivatives; Deacetylated chitosans; Degree of substitution; Degrees of substitution; Fungus growth; In-vitro; Minimum inhibitory concentration; Mycelial growth; Polymer concentrations; Potentiometric titrations; Aspergillus; Bromine compounds; Multilayers; Synthesis (chemical); Titration; Voltammetry; antifungal agent; chitosan; drug derivative; antimicrobial activity; fungus; polymer; thallium; toxin; chemistry; drug effect; microbial sensitivity test; nuclear magnetic resonance spectroscopy; potentiometry; structure activity relation; synthesis; time; Antifungal Agents; Magnetic Resonance Spectroscopy; Microbial Sensitivity Tests; Potentiometry; Structure-Activity Relationship; Time Factors; Fungi